PENGARUH MODEL PROJECT BASED LEARNING (PjBL), CASE BASED LEARNING (CBL) DAN GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA - Yaqin, Ainul; Sabariah; Endah Yulia Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the influence of Project Based Learning (PjBL), Case Based Learning (CBL), and learning styles on student learning outcomes. The research methodology used is a quantitative approach involving experiments. The research subjects were students randomly selected from 5 (five) schools spread across 5 (five) areas of Surabaya to take part in the teaching process using the PjBL and CBL models. Students are identified using a questionnaire divided into three main categories: visual, auditory, and kinesthetic. Research findings show that there is a significant influence of the use of the PjBL and CBL models on student learning outcomes. that the regression model which includes CBL, Learning Style, and PjBL as a whole has a significant influence on Learning Outcomes. This can be seen from the large value of F = 35.762 and Sig. = 0.000, which indicates that this model can explain significant variations in student learning outcomes. Meanwhile, Learning Style does not have a significant influence on student learning outcomes. This is indicated by the p-value = 0.531 (greater than 0.05) and the standard coefficient (Beta) which is very small (0.031). Thus, Learning Style cannot be considered as the main factor influencing student learning outcomes in this model. This study highlights the importance of selecting teaching strategies that align with students' learning styles to maximize performance. The results provide guidance for teachers and students in developing flexible and effective teaching strategies.